PENGARUH DIGITALISASI SISTEM AKUNTANSI (ACCURATE ONLINE) TERHADAP PENYUSUNAN LAPORAN KEUANGAN UMKM JAKET KULIT - Faradisha, Fahreza Eka; Muzakki, Kafidin (JURNAL AKUNTANSI BARELANG, 2025)
This purpose of this research is to ascertain how the Ambon Leather Jacket UMKM financial performance may be enhanced by the digitization of the accounting system via the use of Accurate Online. The method applied in this study is descriptive qualitative using a case study approach. The results of the study indicate that there are no significant obstacles in the implementation of Accurate Online at the Ambon Leather Jacket UMKM. Accurate Online facilitates the company owner in monitoring the company's financial condition and controlling the results of the financial reports produced. Based on the data, this UMKM has a cash balance of IDR 12,934,250 after deducting several expenses, and petty cash of IDR 500,000. In addition, the existing inventory reaches IDR 4,825,000 consisting of unsold merchandise, so that the total assets recorded are IDR 18,259,250. The implementation of Accurate Online at the Ambon Leather Jacket UMKM has been successful and proven to make the preparation of its financial reports more organized, in accordance with the expected objectives of digitalizing the accounting system.